Delirium during Covid-19 pandemic: were we over-reporting an overlooked syndrome? - Garcia de Alencar, Julio Cesar; Barreto Garcez Carvalho, Flávia; Dudy Müller Veiga, Alicia; de Souza Stanzani, Gabriela; Ward Abdalla Maia, Ian; Oliveira J. e Silva, Lucas.; Hiray Pera, Isabella; Tetsuo Yokoy Numakura, Guilherme; Ruivo Santos, Leticia; Junqueira Avelino-Silva , Thiago; et al. (LAJEC - Latin American Journal of Emergency Care, 2022)
Objective: To compare incidence of delirium in Emergency Department in elderly patients admitted for SARS-CoV-2 infection and sepsis for other etiologies. Methods: This observational study analyzed elderly patients (>65 years) from two cohort studies that recruited patients in an urban and academic Emergency Department. The first cohort studied septic patients before Covid-19 pandemic and was conducted between September 30, 2019, and March 17, 2020. The second cohort studied Covid-19 patients between April 8, 2021, and May 28, 2021. Our primary outcome was the incidence of delirium at admission in Emergency Department, which we defined using the Confusion Assessment Method. Results: We included 141 patients in our final analysis, with a median age of 72 (interquartile range: 68 to 79) years and a predominance of the male sex (58%). We identified delirium at admission in 31 participants (21%) in septic non-Covid group and 11 (24%) in Covid-19 group (p=0.70). Conclusion: This present study does not support that elderly patients with Covid-19 have higher risk for delirium at admission in Emergency Department when compared to patients hospitalized with sepsis for other etiologies. Although sepsis for Covid-19 have had more than 28% mortality, Covid-19 was not associated with higher mortality in elderly than sepsis for other etiologies. The study protocol was approved by the local Research Ethics Committee (CAPPESq, protocol number 30417520.0.0000.0068).